Determinación de los efectos de la deriva simulada en aplicación de herbicidas sobre hijuelos de sucesión mediante heridas provocadas por el deshije en banano (Musa AAA) cv. Williams. - Cáceres Calderón, Roberto Gregorio (2016)
Weed control is an important aspect to consider in a banana plantation, mainly controlled by the use of herbicides, among which has glyphosate and glufosinate ammonium, however there is no information about the herbicide that causes less impact On the honey Of succession or of the time that must elapse between the dehydration and the use of herbicides. The present investigation was carried out in order to determine the effects of the simulated drift in different times of application of herbicides on wounds caused during the work of dewatering in the banana plants. The research was carried out between August and October 2016, in the Monte Redondo sector, belonging to Baba, Los Ríos province, at 1 ° 46'04.55 east latitude and 79 ° 39'59.3 longitude north, low The sponsorship of the Tropical Pichilingue Experimental Station of INIAP. A completely randomized design with 2x6 + 1 factorial arrangement was used in 15 replicates, with two herbicides at 6 application times, whose interactions are compared with a control, considering as replicates to each plant. Plant growth, pseudotallo circumference and leaf emission data were evaluated, which showed that glyphosate allowed a greater growth of plants, registering a plant height of 107.8 cm. The circumference of the pseudotallo was mayor when applying glufosinate of ammonium, allowing to obtain plants with circumference of pseudotallo of 22.15% more than those treated with glyphosate. When the herbicides were applied immediately after the dehistance, a greater growth and circumference of the pseudotallo was achieved with 116.1 and 39.3 cm, respectively. When Glyphosate was applied immediately after the break, it obtained higher plants that grew in an average of 119.5 cm. The application of ammonium gluten at the time of thawing, production plants with the thickest pseudotallo with a circumference length of 42.5. cm. The leaf emission was not influenced by any of the herbicides, nor by the different times of application. Keywords: banana, herbicides, glyphosate, ammonium glufosinate.